Primary Chondroblastic Osteosarcoma of the Uterus: Immunohistochemical Examination and Differential Diagnosis with Malignant Mixed Mullerian Tumor - Gülzade Özyalvaçlı (İstanbul Medical Journal, 2015)

(untitled)
Extraskeletal osteosarcomas are rarely observed tumors. Besides this, primary osteosarcomas of uterus are rarer, and only 21 cases have been reported in the literature. It is generally seen at the postmenopausal period, and it progresses quite aggressively. Particularly, malignant mixed mullerian tumors (MMMTs) are important for differential diagnosis. Histopathological and immunohistochemical examination of a mass that was detected in the uterus of a 61-year-old postmenopausal patient revealed the diagnosis of primary chondroblastic osteosarcoma, and this very rare case is presented here.